Limitación de la procedencia del embargo de acciones y participaciones de socios de compañías de responsabilidad limitada “Cías. Ltda” en procesos judiciales - Paucar Pizarro, Joan Enrique (2024)
This Curricular Integration Project proposes a legal, doctrinal and comparative law analysis as to the appropriateness and execution of the precautionary measure of seizure of shares and participations belonging to a partner of a limited liability company in judicial proceedings. The interest in investigating and carrying out this analysis arises from the review of the legal regulations in force and judicial proceedings where irregularities in the compliance of judicial resolutions by the defendant, who is a partner of this type of mercantile company, are found due to a legal inconsistency in the Company Law that limits the proceeding and execution of the attachment as a precautionary measure since the unanimous consent of the capital stock is previously required for the shares and participations of a partner to be pledged and the corresponding proceedings to continue for the compliance of an obligation demanded through judicial proceedings, This is evidence of the violation of the right to effective judicial protection of the rights and particular interests of the plaintiff, which also entails the violation of the guarantees of due process, principles of administration of justice and legal certainty, since there is no concordance between the relevant regulations. This academic activity was developed using research materials and methods, physical and digital bibliographic sources, surveys and interviews with practicing lawyers. It was established that the precautionary measure of attachment should be of effective application and without limitations. With the documentary observation of case studies, it was determined that by limiting the applicability of the precautionary seizure measure with a prior consent of the entire capital stock, the application of the adjective regulation that ensures the compliance of an obligation owed by the defendant is restricted. Therefore, it is necessary to reform the Law of Companies in order to guarantee the proceeding and execution of the seizure of shares and participations belonging to partners of limited liability companies in order to protect the compliance of rights and interests of individuals who file a judicial proceeding against them.